PENGARUH METODE DAN WAKI'U PENYULINGAN TERHADAP RENDEMEN DAN SIFAT FISIKO KIMIA MINYAK KENANGA - Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
This paper described the study on the effect of distilling time and methods on yield and pysiocheical properties of cananga oil. The distillation methods applied were water distillation an water steam distillation with the distilling time being 8, 16, and 24 hours, consecutively. The results were analysed using the randomized completely block design, and the difference between means were tested with the Least Significant Difference method.The results showed that the distilling method appeared to have significant effect on the saponification and ester numbers whereas, the oil yield was significantly increased with prolonged distilling time. Water distillation method produced higher quality of cananga oil than that produced by the water-steam distillation one. This was indicated by a higher ester number of the oil obtained by the water distillation.